2001
DOI: 10.1093/humrep/16.9.1970
|View full text |Cite
|
Sign up to set email alerts
|

The Graduated Embryo Score (GES) predicts blastocyst formation and pregnancy rate from cleavage-stage embryos*

Abstract: Predicting which cleaved embryos will form blastocysts could permit the high success rates associated with blastocyst transfer to be achieved from day 3 embryo transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 16 publications
3
84
0
3
Order By: Relevance
“…On days 3 or 5 after oocyte retrieval, depending on the number of good quality embryos, a total of 1-3 embryos were transferred into the uterine cavity under the ultrasound guidance with a flexible catheter (Wallace; Irvine Scientific, Santa Ana, CA). Embryo scoring was performed as described previously [5]. Total number of oocytes was defined as the total number of oocytes collected at oocyte pick-up.…”
Section: Methodsmentioning
confidence: 99%
“…On days 3 or 5 after oocyte retrieval, depending on the number of good quality embryos, a total of 1-3 embryos were transferred into the uterine cavity under the ultrasound guidance with a flexible catheter (Wallace; Irvine Scientific, Santa Ana, CA). Embryo scoring was performed as described previously [5]. Total number of oocytes was defined as the total number of oocytes collected at oocyte pick-up.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were evaluated on Day 2 and Day 3 of culture, and were scored using either a new combined scoring system (CSS) or a traditional cumulative embryo score (CES) system. The CSS is a modification of the graduated embryo scoring system (Fisch et al, 2001; and is the combination of evaluations of early development at three intervals: the presence of nucleolar alignment along the pronuclear axis 16~18 h after insemination, the presence of regular and symmetrical cleavage 25~29 h after insemination, and cell number and fragmentation on Day 3 of culture. A detailed description of CSS is shown in Table 1.…”
Section: Ivf Procedures and Embryo Evaluationmentioning
confidence: 99%
“…Multiple studies of embryo morphology have identified features indicative of better implantation potential in fresh cycles using cleavage-stage embryos [4][5][6][7]. Embryos with eight blastomeres or at compacting stage on day 3 generally have been shown to perform better than those with fewer blastomeres [5].…”
Section: Introductionmentioning
confidence: 99%